Strategy of the Depok City Government, Indonesia on Waste Management Towards a Zero Waste City - Putri, Dhika Kusuma; Sepkamala, Diva Deda; Rahman, Abdul (Universitas Muhammadiyah Yogyakarta, 2025)
The Kota Tanpa Sampah (Waste-Free City) program, launched in Depok City in 2016 and scheduled to continue until 2024, is a comprehensive waste management policy aimed at eliminating waste from various areas of the city. Based on its source, waste management in Depok City is segregated into three categories: organic, inorganic, and residue. Despite its sustainable goals, the program faces significant challenges in its implementation, resulting in ongoing waste management issues in various areas. One such example is the Cipayung landfill, where poor waste management practices have resulted in a deplorable accumulation of waste, resembling a garbage dump. This research aims to explore the Depok City Government's Strategy in Waste Management Towards Achieving a zero-waste city. Using the literature study method and descriptive data analysis approach as proposed by Creswell and Creswell, the investigation revealed that the Zero Waste Program has not reached its maximum potential. The findings indicated that waste management continued to be a significant concern for the city.